Manejo de Calepitrimerus vitis (Nalepa, 1905) (Acari: Eriophyidae) em videiras na Região da Campanha do Rio Grande do Sul - Siqueira, Paulo Ricardo Ebert (2010)
The presence of Calepitrimerus vitis (Nalepa, 1905) in vineyards in the countryside of Rio Grande do Sul was verified from the 2004/2005 harvest associated with symptoms of tanning on the leaves. In Brazil there are no recommendations for monitoring of this mite, just as there is no acaricide recommended for management of the species in vineyards. To detect differences in infestation of C. vitis among cultivars was conducted the monitoring of population fluctuations of C. vitis vinifera cultivars Chardonnay and Merlot, in a commercial vineyard in Dom Pedrito, RS, during the years 2005/2006 and 2006/2007, in order to identify differences in infestation between cultivars of a crop year to another. It was observed that the cultivars Chardonnay and Merlot, the population peaks of C. vitis occurred between late February and early March and there is a high correlation between the number of C. vitis found on the underside of the leaves and the percentage of leaves with the species. In the greenhouse, during the years 2006/2007 and 2007/2008 was evaluated the efficiency of sticky traps to monitor C. vitis in cuttings for propagation, comparing catches in cuttings derived from nurseries and vineyards with different histories of infestation. We observed that the sticky traps to detect the presence in the cuttings of C. vitis. During the crop years 2007/2008 and 2008/2009 was conducted the monitoring of population dynamics of C. vitis in Cabernet Sauvignon, in a commercial vineyard located in the town of Candiota-RS, through the use of sticky traps and direct observation on the abaxial surface of leaves. As observed in the Dom Pedrito-RS, Candiota-RS was observed a significant and high correlation (r ² ≥ 0.95) between the number of C. vitis on the abaxial surface of leaves and percentage of leaves with the mites. The sticky traps used for monitoring were more efficient in detecting C. vitis during periods of high and low population levels. Was evaluated in a commercial vineyard, insecticides and acaricides in order to reduce the population of C. vitis in autumn and in spring 2008 and autumn 2009. The acaricides spirodiclofen and cyhexatin were the most promising in reducing the infestation during the autumn. The use of sulfur in a single autumn spray or two sprays, one in autumn and another in the spring, effectively controlled C. vitis in the spring. The use of acaricides abamectin and spirodiclofen a single spring spray or two sprays, one in autumn and another in the fall and spring, effectively controlled the population of C. vitis in the spring. The acaricides abamectin, azadirachtin, cyhexatin, sulfur and spirodiclofen evaluated for control of C. vitis were tested for selectivity to predatory mite Neoseiulus californicus (McGregor, 1954). It was found that 24 hours after application in vineyard acaricide cyhexatin was slightly harmful, and all other products tested as harmless. From the third day of application in the vineyards all products were harmless to N. californicus, to cause mortality under 30%